Establishing a Blockchain-based Architecture for Fake News Detection - Graciano-Neto, Valdemar Vicente; Barbosa, Jacson Rodrigues; Lima, Eliomar Araújo de; Cintra, Luiza Martins de Freitas; Venzi, Samuel; Kassab, Mohamad (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS), 2024)
Fake News are a contemporary phenomenon with potential devastating effects. For inquiry and auditability purposes, it is essential that the news, once classified as false, can be persisted in an immutable means so that interested parties can query it. Although Blockchain clearly satisfies the main requirements for Fake News Management Software Systems, the prescriptive architectural solutions for that domain that cohabit Blockchain with other technologies in a single proposal still need to be made available. This paper’s main contribution is presenting a prescriptive architectural solution for blockchain-based fake news management software systems. The Hoffmeister process for software architecture design is systematically followed to culminate in a software solution for that domain. The implementation of a candidate architecture and a brief simulation-based evaluation show the feasibility of the solution to satisfy the functional and quality requirements.